Avaliação antropométrica e do consumo alimentar de indivíduos com doença celíaca do ambulatório de gastroenterologia pediátrica do Hospital das Clínicas, UFMG - Marina Magalhães de Sousa e Silva (2013)
Celiac disease (CD) is an autoimmune disease triggered by the presence of wheat gliadin and similar proteins in barley and rye in the diet of susceptible individuals. Wheat is an important source of vitamins and minerals. The treatment for celiac disease is to follow a gluten-free diet, so it is important to lead these individuals to nutritional counseling. Non-adherence to the diet by the patient can lead to nutritional deficiencies, obesity and increased incidence of malignancies. The sooner is started the gluten-free diet, the better are the results in the recovery of body composition. There are few studies in Brazil that address the nutritional aspects of celiac disease patients and their body changes. Objective: Evaluate the nutritional profile of celiac disease patients treated at the Clinic of Pediatric Gastroenterology at the Hospital of Minas Gerais University (UFMG) through anthropometry and food intake assessment. Methods: We evaluated 31 patients with celiac disease from three to 23 years old and 31 healthy individuals from three to 23 years. The sample was chosen by convenience. We collected weight, height, waist and hip circumference and BMI was calculated. The body fat percentage, muscle mass and total body water were measured by bioelectrical impedance analysis. For analysis of food intake we applied food frequency questionnaire, dietary records and 24 hour dietary recall. The same information was collected for the control group for comparison between groups. Results and Discussion: According to food intake, calorie and lipids consumption was higher (p < 0.05) in the study group. Carbohydrate intake was greater (p < 0.05) in the control group. There was no statistical difference between the two groups for protein intake, saturated fat, trans fat, cholesterol or fiber. The average intake of folate and vitamin B1 was higher (p < 0.05) in the study group, and the average intake of vitamin B2 was higher (p < 0.05) in the control group. The average intake of sodium and zinc was higher (p < 0.05) in the study group and magnesium was higher (p< 0.05) in the control group. Despite the difference in the amount ingested, the proportion of subjects who achieved the daily requirement for vitamins and minerals according to the IDRs selected were similar between both groups. According to anthropometric analysis we have found no significant differences (p < 0.05) between the two groups. The proportions of individuals with body parameters above, below or proper, under the tracks proposed by international health organizations, were similar. Conclusion: Patients with celiac disease, which follows a gluten-free diet, have normal body composition if they have a diet rich in macro and micronutrients. The gluten-free diet was not proved, in this study, as detrimental for the body composition of these individuals. The composition of the diet of celiac patients was similar, and some items more suitable than that of the control group. There were no statistical differences between the body composition of the two groups. The elaboration of further studies is encouraged to relate the influence of long term gluten-free diet on the nutritional status of such patients.